Implementation of SDG#5 and #17 into Women-oriented Products for Co-Branding - Yeung, Shirley Mo Ching (Journal of Ecohumanism, 2025)
The aim of this paper is to explore the elements of shared vision with SDGs elements for sustainable co-branding. A qualitative research was conducted with ESG scores under S & P for Wacoal Holdings – Environmenal 33/ industry mean 25, Social – 23/ industry mean 28 and Governance 35/ industry mean 29. Based on the study, various scores of different categories were examined and the strong areas are environmental and governance while the improvement areas identified are: sustainable marketing and brand perception/ occupational health and safety (0 Wacoal score /21 industry mean score and 10 Wacoal score /24 industry mean). Hence, it is suggested to explore the social engagement via co-branding with shared vision for improving the score in sustainable marketing, for example, the case of Wacoal Hong Kong. Through this paper, management of service organizations may explore the decision-making process of co-branding for empowering women with social engagement, and the use of technology for communmity engagement with AI, digital contents with intellectual property rights via art elements for the well being of employees. Finally, the co-branding may lead to improve social engagement for sustainable business.